BIOMARKERS IN EARLY DETECTION OF CHRONIC KIDNEY DISEASE - DIAGNOSTIC PERFORMANCE AND CLINICAL UTILITY - Abdurashidov Akhorjon Akhmatjon ugli (Web of Journals Publishing, 2025)
Chronic kidney disease remains underdiagnosed in early stages when intervention proves most effective. This study examines novel biomarkers including neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, and cystatin C for detecting early renal dysfunction. Analysis of diagnostic performance demonstrates superior sensitivity compared to traditional creatinine-based assessment, with NGAL showing 87.4% sensitivity at stage 1 disease. These biomarkers enable detection 6-12 months earlier than conventional methods, offering substantial clinical benefit for intervention timing and disease management.
Keywords: nephrology, creatinine, cystatin, NGAL, KIM-1, albuminuria, glomerular, proteinuria, diagnosis, sensitivity, specificity, nephropathy, urinalysis, pathophysiology